2018
DOI: 10.3114/fuse.2018.01.05
|View full text |Cite
|
Sign up to set email alerts
|

Postia caesia complex (Polyporales, Basidiomycota) in temperate Northern Hemisphere

Abstract: Taxonomy of the Postia caesia complex is revised based on morphology and two genetic markers, ITS and tef1. In total, we recognize 24 species, multiplying the known species diversity in the complex. We provide descriptions for 20 temperate Northern Hemisphere taxa. Identity of the core species, P. caesia, is re-established, and a neotype from the type locality is selected. Four new combinations are proposed, and 10 new species are described:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
58
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(61 citation statements)
references
References 23 publications
3
58
0
Order By: Relevance
“…This is in accordance with other comparable studies on polypores (e.g. Otrosina and Garbelotto 2010, Spirin et al 2015, Han et al 2016, Song and Cui 2017, Spirin et al 2017, Miettinen et al 2018). Notable exceptions here include S. semipileata , which has a circumpolar distribution and S. nivea , which ranges longitudinally from northern China to New Zealand.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…This is in accordance with other comparable studies on polypores (e.g. Otrosina and Garbelotto 2010, Spirin et al 2015, Han et al 2016, Song and Cui 2017, Spirin et al 2017, Miettinen et al 2018). Notable exceptions here include S. semipileata , which has a circumpolar distribution and S. nivea , which ranges longitudinally from northern China to New Zealand.…”
Section: Discussionsupporting
confidence: 94%
“…Carlson et al 2014, Miettinen et al 2018) who conclude that tef1 is more variable between species than ITS and provides greater resolution in separating species. Still, unique character state combinations can be identified from ITS sequences even for the most closely related species in the S. nivea complex.…”
Section: Discussionmentioning
confidence: 99%
“…It needs to be mentioned here that species recognition in Antrodiella is based on very slight sequence differences (which is also the case for many other polypores, see Miettinen et al 2018), in this case mostly in the ITS2. The two identical sequences we obtained for A. cf.…”
Section: Molecular Delimitation and Identification Of The Otus (Or Tementioning
confidence: 94%
“…Because the use of molecular sequence data (Miettinen et al 2018) suddenly revealed the existence of many 'cryptic' northern hemisphere species, the ARCS-which contained many morphology-based records for Postia/ Oligoporus species-decided to eliminate all records from this Atlas in the absence of available sequence data to identify these Postia records from Switzerland more reliably. Our sequence therefore suddenly becomes the first positive species identification for the country in this species complex.…”
Section: Molecular Delimitation and Identification Of The Otus (Or Tementioning
confidence: 99%
See 1 more Smart Citation